Mid-long term optimization of reservoir operation for hybrid pumped storage power station based on stochastic dynamic programming - Li, Wen-Wu; Wu, Xi-Xi; Huang, Jin; Ma, Qiang; Guo, Xi-Hai (Dianli Xitong Baohu yu Kongzhi, 2013)
Because of the uncertainty of the natural runoff of reservoir, a mid-long term reservoir operation stochastic optimization model is established for the hybrid pumping storage power station based on describing the stochastic process of runoff, which takes the maximum energy generating expectation as its objective. The stochastic dynamic programming algorithm has two control variables: water flow and pumping time. Case study of Baishan mixed pumped storage units shows the energy generating expectation of scheduling period increases from 2 165 million kW upsilon .h to 2 463 million kW upsilon .h, the guaranteed output increases by 12 MW, and the water level is slightly higher in all periods. At the same time, compared with the model established by the long series of law, the stochastic model obtains better results and the model can better reflect the randomness of the natural runoff, even more practical.